Pengaruh Media Film Animasi Larva Terhadap Kemampuan Menulis Paragraf Argumentasi pada Siswa Kelas IV SD Hang Tuah I Belawan Tahun Pembelajaran 2023/2024 - Danis, Amir; Pratiwi, Andini Puspa (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2024)
Writing is a skill that rarely gets attention from teachers, even though writing activities are an effective form of training to help students use and master Indonesian correctly. Factors that can support the successful delivery of information are the use of media that is displayed in a simple and easy way for students to understand. Digital media that can be used to convey information is the animated film